PERBANDINGAN PERILAKU BALOK TANPA SAMBUNGAN LEWATAN DAN BALOK DENGAN SAMBUNGAN LEWATAN - Sulastri Sulastri (Fakultas Teknik Universitas Borobudur, 2020)
Placement and strength of joints must be planned well so as not to cause collapse in the structure. Lap splices the reinforcement must be able to transfer the forces acting on the reinforcement due to the load given. This study investigates the behavior of beams without lap splices and beams with lap splices. Specimens consist of two beams, namely beams without lap splices and beams with extended joints with lap splices (ld) of 640 mm. The test is carried out with a pure bending test method with loading of Two Point Loads on a simple support beam. From this study, the maximum flexural load on the beam without a connection is obtained from 115.41 kN with a maximum deflection of 16.41 mm. For beams with a channel length of 640 mm, the maximum bending load of 124.804 kN was obtained with a deflection of 25.02 mm. The results showed that the reinforced bonding joints that were properly implemented were able to channel the forces acting on the reinforcement until the beam reached its capacity.Keywords: splice length; lap splices; bending strength ; concrete beam test; deflection